The lovers [videorecording (DVD)] - Jacobs, Azazel; Winger, Debra, 1955-; Letts, Tracy, 1965-; Gillen, Aidan, 1968- (A24 Films, 2017)
Mary and Michael are a long married, dispassionate couple who are both in the midst of serious affairs. On the brink of calling it quits, a spark between them suddenly reignites, leading them into an impulsive romance.